Evasive Higgs boson maneuvers at the LHC - Englert, Christoph; Jaeckel, Joerg; Re, Emanuele; Spannowsky, Michael (Physical review. D, Particles, fields, gravitation, and cosmology, 2012)
Nonstandard decays of the Higgs boson produced at the Large Hadron Collider can lead to signatures which can easily be missed due to nonadapted trigger or search strategies. Keeping electroweak symmetry breaking standard model-like, we classify the phenomenology of an evasive Higgs boson into three categories and discuss how they can be described in an effective field theory. We comment on how one can improve the search strategies to also detect such an evasive Higgs.